PROMOSI JABATAN DAN LINGKUNGAN KERJA NON FISIK DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA GOLDEN TULIP BAY VIEW HOTEL & CONVENTION BALI KUTA SELATAN BADUNG - Ni Made Gunastri; I Gusti Gede Oka Pradnyana (KRISNA: Kumpulan Riset Akuntansi, 2018)
In order to face the business world that is full of competition, a company leader needs to do any efforts to look for a new paradigm and to define his business strategy, so the business can still survive, flourish and develop, while it is also expected to keep creating a conducive working environment. In general, once a person has been accepted, placed and employed by a company, then the next duty of a manager is to evaluate his or her performance. To set this policy later means whether that employee will be promoted, demoted and or got a remuneration. A promotion contributes to an important role for each of employee and even it becomes something that they always wait for. With this job promotion, it means there is a belief and acknowledgement related to the abilities and proficiency of the employees to occupy a higher level of position. This research is aimed to 1) test and analyze the impacts of job promotion on the performance of employees at Golden Tulip Bay View Hotel & Convention Bali; 2) test and analyze the impacts of non-physics working environment at Golden Tulip Bay View Hotel & Convention Bali; 3) test and analyze the influences of job promotion and non-physical job environment on the employees working at Golden Tulip Bay View Hotel & Convention Bali. This research used a survey designed to include respondents in overall 88 hotel employees. The samples were taken by using probability sampling technique that was called proportionate stratified random sampling. The test of hypothesis used was a multiple linear regression analysis with a data analysis entirely had been processed through SPSS version 17.0 program. The first hypothesis result shown that the job promotion had positively and significantly influenced on the performance of employees with t value counted was 4.249 and with significant level of 0.000. The second hypothesis described that the non-physical job environment had positively and significantly influenced to the performance of employees with t value counted was 5.550 and significant level of 0.000 that was smaller than 0.05. By looking at the standardized coefficient beta, the job promotion variable has taken into 0.395 and for the non-physical job environment variable was 0.423, so then it can be concluded that the non-physical job environment had a dominant influence on the performance of employees. This has been supported by the third hypothesis examination shown that both of the job promotions and non-physical job environment simultaneously had been influencing a positive and significant value on the performance of employees, as it seemed from the F value counted; it broke into 49.648 and with significant level of 0.000. Key words : job promotion, non-physical job environment, performance of the employees.